(untitled) (European Journal of Pure and Applied Mathematics, 2024)
This paper is concerned with the concepts of upper and lower almost (τ_1,τ_2)-continuous multifunctions. Furthermore, some characterizations of upper and lower almost (τ_1,τ_2)-continuous multifunctions are investigated.